STRATEGIC COMPETITIVENESS IN THE ERA OF DIGITAL TRANSFORMATION: A SYSTEMATIC REVIEW ON THE EVOLUTION OF STRATEGIC MANAGEMENT APPROACHES - Rokhmad M. Rofiq; Annisa Retno Utami; Lazuardi Fachrul Nizar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to identify dominant theoretical and practical trends in strategic management literature in the digital transformation era and to explore emerging research gaps. Utilizing a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines, this research analyzes 42 Scopus-indexed journal articles published between 2020 and 2024. The findings, supported by bibliometric analysis using VOS viewer, reveal three major clusters: digital transformation and innovation strategy, strategic competitiveness through dynamic capabilities, and digital sterilization with platform-based strategies. These clusters reflect a paradigm shift from conventional resource-based and industrial-organization approaches to strategies that are adaptive, technology-driven, and collaborative. Furthermore, the study highlights significant gaps in integrating digital-based strategies within mainstream strategic management theories, with limited attention to concepts such as design thinking, ecosystem strategy, and AI-enabled decision-making. This study contributes theoretically by mapping the evolution of strategic thinking aligned with digital disruption, and practically by offering strategic insights for organizations aiming to sustain competitiveness in rapidly evolving markets. The results emphasize the urgency for organizations to adopt flexible, data-driven strategies that integrate innovation, digital capability, and ecosystem collaboration as central pillars of long-term strategic success